2012
DOI: 10.1124/dmd.112.046268
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative ipso Substitution of 2,4-Difluoro-benzylphthalazines: Identification of a Rare Stable Quinone Methide and Subsequent GSH Conjugate

Abstract: ABSTRACT:In vitro metabolite identification and GSH trapping studies in human liver microsomes were conducted to understand the bioactivation potential of compound 1 [2-(6-(4-(4-(2,4-difluorobenzyl)phthalazin-1-yl)piperazin-1-yl)pyridin-3-yl)propan-2-ol], an inhibitor of the Hedgehog pathway. The results revealed the formation of a unique, stable quinone methide metabolite (M1) via ipso substitution of a fluorine atom and subsequent formation of a GSH adduct (M2). The stability of this metabolite arises from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…The fluorination pattern of the hedgehog pathway inhibitor 452 was designed to reduce the electron density of the benzyl moiety and thereby lower its susceptibility to oxidative metabolism . However, metabolite profiling studies with 452 in HLM identified a metabolite, proposed to be the quinone methide 454 , that formed during oxidative defluorination of the benzyl moiety.…”
Section: Fluorinated Aromaticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fluorination pattern of the hedgehog pathway inhibitor 452 was designed to reduce the electron density of the benzyl moiety and thereby lower its susceptibility to oxidative metabolism . However, metabolite profiling studies with 452 in HLM identified a metabolite, proposed to be the quinone methide 454 , that formed during oxidative defluorination of the benzyl moiety.…”
Section: Fluorinated Aromaticsmentioning
confidence: 99%
“…This arene oxide would rearrange to 454 , a compound that is stabilized by resonance delocalization of the lone pair of electrons on the piperazine N atom. An alternative proposal envisioned H atom abstraction by P450 from the benzylic site and subsequent oxidation of the delocalized radical . In addition to the quinone methide 454 , a GSH adduct of undefined regiochemistry, 455 , was identified along with a hydroxylated analogue of this metabolite .…”
Section: Fluorinated Aromaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Transformation genügte jedoch nicht, um die beschriebene Situation zu verbessern. CYP‐vermittelte ipso ‐Defluorierungen laufen leicht unter Bildung von 184 und 185 ab, wie durch LC/MS und Glutathion‐Abfangstudien bestätigt wurde . Mit diesem Beispiel soll verdeutlicht werden, dass der Ersatz eines Wasserstoffatoms durch ein Halogenatom mitnichten eine unfehlbare Strategie ist, um die Ausscheidung zu verringern oder um die Bildung reaktiver Zwischenprodukte zu vermeiden.…”
Section: Andere Anwendungen: Strategien Zur Verhinderung Des Metabolunclassified
“…In most cases, the formation of glutathione-S-conjugates results in cellular detoxification of free radical intermediates, however, in some instance glutathione-S-conjugates can result in bioactivation leading to generation of potentially toxic metabolites [ 10 ]. Several groups have reported novel sites of glutathione conjugations in diaminothiophene [ 11 ] via stable quinone methide intermediates [ 12 ].…”
Section: Introductionmentioning
confidence: 99%